Evaluation of OHS Implementation and Documentation in Road Construction Projects - Varela, Jony Rodrigues; Radjawane, Louise Elizabeth (Metromedia, 2025)
This study investigates the practical realities and persistent challenges in occupational health and safety (OHS) implementation on road construction projects, with a particular focus on the barriers between regulatory frameworks and workplace outcomes. Adopting a qualitative literature review and thematic synthesis methodology, the research examines both the operational compliance with OHS mandates and the systemic issues impeding accurate reporting and evaluation. Findings reveal that there are inconsistencies between regulatory expectation and field-level practice due to administrative routines, limited managerial engagement, and fragmented communication channels. Furthermore, underreporting of incidents and inadequate documentation limit the sector’s ability to leverage data for risk mitigation and continuous improvement. The evidence suggests that that overcoming these obstacles requires organizational transformation, including participatory leadership, continuous digital integration, and cultivating mutual trust among all project stakeholders. Recommendations outlined in this analysis include fostering routine group training, developing accessible reporting systems, and embedding reflective learning mechanisms. This review not only underscores the criticality of cultural and systemic reform in building a sustainable safety culture but also contributes actionable knowledge for policymakers, managers, and practitioners dedicated to meaningful advancement in road construction safety.